Pengaruh Good Governance dan Stabilitas masa kerja of Personel Terhadap Implementasi Anggaran Berbasis Kinerja dengan Komunikasi Sebagai Variabel Moderating - Andria Dartana; Eka Nurmala Sari; Hastuti Olivia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Good Governance and employee tenure stability on the implementation of performance-based budgeting, as well as to evaluate the role of communication as a moderating variable in the Regional Financial Management Agency (BPKD) of Southeast Aceh Regency. The background of this study is based on the decline in the regional budget realization rate from 96.15% in 2022 to 89.39% in 2024, as well as issues related to transparency, accountability, employee rotation, and communication effectiveness. This study uses a quantitative approach with an associative method. The study took the entire population into a sample of 80 respondents. Data collection was carried out through questionnaires, interviews, documentation, and observation, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3.0 software. The results of the analysis show that Good Governance has a positive and significant effect on the implementation of performance-based budgeting (t = 4.757; p = 0.000). Likewise, employee tenure stability had a positive and significant effect (t = 3.453; p = 0.001). Furthermore, communication was shown to significantly and positively moderate the relationship between Good Governance (t = 3.865; p = 0.000) and employee tenure stability (t = 3.776; p = 0.000) and performance-based budget implementation. The results showed that effective communication positively influenced Good Governance and tenure stability in performance-based budget implementation. In conclusion, successful budget implementation requires strengthening Good Governance, strategic tenure management, and more communicative and effective communication.